Final inversion of the Midcontinent Rift during the Rigolet Phase of the Grenvillian Orogeny - Hodgin, Eben B.; Swanson-Hysell, Nicholas L.; DeGraff, James M.; Kylander-Clark, Andrew R.C.; Schmitz, Mark D.; Turner, Andrew C.; Zhang, Yiming; Stolper, Daniel A. (Digital Commons @ Michigan Tech, 2022)
Despite being a prominent continental-scale feature, the late Mesoproterozoic North American Midcontinent Rift did not result in the break-up of Laurentia, and subsequently underwent structural inversion. The timing of inversion is critical for constraining far-field effects of orogenesis and processes associated with the rift’s failure. The Keweenaw fault in northern Michigan (USA) is a major thrust structure associated with rift inversion; it places ca. 1093 Ma rift volcanic rocks atop the post-rift Jacobsville Formation, which is folded in its footwall. Previous detrital zircon (DZ) U-Pb geochronology conducted by laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) assigned a ca. 950 Ma maximum age to the Jacobsville Formation and led researchers to interpret its deposition and deformation as postdating the ca. 1090–980 Ma Grenvillian Orogeny. In this study, we reproduced similar DZ dates using LA-ICP-MS and then dated 19 of the youngest DZ grains using high-precision chemical abrasion–isotope dilution–thermal ionization mass spectrometry (CA-ID-TIMS). The youngest DZ dated by CA-ID-TIMS at 992.51 ± 0.64 Ma (2σ) redefines the maximum depositional age of the Jacobsville Formation and overlaps with a U-Pb LA-ICP-MS date of 985.5 ± 35.8 Ma (2σ) for late-kinematic calcite veins within the brecciated Keweenaw fault zone. Collectively, these data are interpreted to constrain deposition of the Jacobsville Formation and final rift inversion to have occurred during the 1010–980 Ma Rigolet Phase of the Grenvillian Orogeny, following an earlier phase of Ottawan inversion. Far-field deformation propagated >500 km into the continental interior during the Ottawan and Rigolet phases of the Grenvillian Orogeny.